PERENCANAAN ULANG BANGUNAN PENGAMBILAN BERTIPE MORNING GLORY MENGGUNAKAN PONDASI BORED PILE PADA BENDUNGAN LOGUNG - Moch. Suaib Reiza; Agus Suhardono; Musa Pranadesta Manzra Surati (Prokons: Jurnal Teknik Sipil, 2019)
The existing square tower of intake has 1,397.57m3 volume and using shallow foundation Logung Dam with its weight stability will cause inefficient structures and potential to earthquake force effect. It is necessary to have an alternative planning of the intake tower. The authors intends to redesign the intake with morning glory type and used bored pile; to find out the position of intake tower, dimension, reinforcement, duration, cost estimate, and to compare the redesign.The required data were of topographic map, irrigation, and raw water discharge, bearing capacity, and work unit price analysis of project 2016. Manning Method was applied to find out the dimension; Shell Slab Method with Column Approach to calculate the structure of the intake tower, and Skempton Method to calculate bearing capacity. The redesign results in the position of ∅ 1.75-m intake tower on conduit channel with 728,08 m3 volume; the dominant load of  operational-earthquake combination with different values; D22-200 steel bar for y-direction, D19-150 for x-direction on conduit channel, D19-150 for x,y-direction on intake tower segment 1, D16-150 for x,y-direction on intake tower segment 2, and D13-150 for x,y-direction on intake tower segment 3; on 105 workdays; at  a total cost of IDR 2,327,806,700 with 40.64 % efficiency cost.